TRANSNATIONAL CORPORATIONS AND ECONOMIC GROWTH IN NIGERIA - Nma Okechukwu, Okoroji; Chinedu, Egbunike; Nonso, Okoye; Widiyanti, Marlina (Faculty of Economic and Business, University of Pasundan, 2023)
Prior studies have mainly attributed the reason for suboptimal economic growth rate in Sub-Saharan Africa as home-made majorly caused by misguided economic policies which have distorted the flow of Foreign Direct Investment (FDI) inflows to the region despite efforts of Transnational Corporations in the region and its growing presence in her core sectors. In view of these, the main objective of this study is to examine the relationship between Gross Domestic Product and economic growth in Nigeria. The study is anchored on Internalization Theory. The study relied on secondary sources of data obtained from CBN Statistical Bulletin and National Bureau of Statistics for the period 1999-2018. The data was analysed using descriptive and inferential statistics. The results revealed a significant positive effect of FDI inflows on Gross Domestic Product in Nigeria. Based on this, the study recommends among others that the need for government to woo more of transnational firms in the various sectors of the economy in order to gain the advantage of technology transfer to Nigeria.